EFEKTIVITAS INTERVENSI PSIKOEDUKASI TERHADAP KEPATUHAN BEROBAT PASIEN SKIZOFRENIA - Sulung, Neila; Foresa, Nice (REAL in Nursing Journal, 2018)
Psychoeducation is one form of intervention, both for families and clients who are part of the psychosocial therapy. Psychoeducation aims to increase knowledge about schizophrenia patients and families and to improve treatment compliance. This study aims to determine the effectiveness of psychoeducation intervention for treatment compliance of schizophrenia patient. The kind of this research is quasiexperimentalwith control group design with 16 samples that was selected by pusposive sampling, consist of 8 people was the experimental group that was given psychoeducation intervention and 8 people was the control group that was given health education. The datawas collected by filled the observation sheet as much as 12 statements.  The Test that used was T-Test Independent with p value <0.05. The result of this research is the mean of treatment compliance on experimental group is 11,00 and control group 6,88. In statistic test showed that there is the significant difference between treatment compliance of schizopheria patient on experimental group and control group with p value 0,0005 (p < 0,05).Based of the result above can be concluded than psychoeducation intervention more effective to increase the treatment compliance of schizophrenia patients than health education. It is recomended to the nurse in health center to implements this psychoeducation regularly in gives nursing care to schizophrenia patients. Keywords         : psychoeducation, treatment compliance, schizophrenia